Awake and Sleep Oral Behaviours in Patients With Painful Temporomandibular Disorders - Keela W. (2023)
Objectives: The aim of this research was to explore the oral behaviours exhibited by individuals with and without temporomandibular disorders (TMD) pain, and with various pain characteristics; and to determine which oral behaviour is correlated with painful TMD. Methods: 328 patients with TMD who visited Orofacial Pain Clinic were included in this retrospective cross-sectional study. The patients were categorised into 2 groups—painful TMD and non-painful TMD—based on pain status; their other pain characteristics were recorded. To evaluate oral behaviours, researchers utilised the Oral Behaviors Checklist (OBC) and categorised into 3 levels based on the Diagnostic criteria for TMD scoring manual. To investigate the associations amongst demographic information, oral behaviour levels, and TMD pain status and characteristics, logistic regression was employed, whilst t tests were used to analyse OBC scores. Logistic regression was also used to examine individual oral behaviours in relation to specific pain characteristics. Results: Age and marital status were associated with TMD pain status. Significantly higher OBC scores were observed in chronic pain compared to acute pain group, but the scores were not significantly different for pain status and other pain characteristics. OBC score and level were associated solely with TMD pain chronicity. According to multivariate logistic regression, “clench or grind teeth when sleeping” was the strongest predictor of TMD pain and “place tongue forcibly against teeth” was the strongest predictor of chronic painful TMD. Conclusions: High oral behaviour level and OBC scores were associated with chronic painful TMD. Sleep bruxism was the strongest predictor of TMD pain. Age and marital status were correlated with TMD pain status. In the treatment of TMD, there can be potential benefits in addressing and managing oral parafunctional behaviours.